Primary School Teachers’ Readiness for Inclusive Education Implementation: A Multidimensional Analysis of Competence, Self-Efficacy, and Instructional Challenges - Apsarendra Putra; Kadek Suranata; Ni Kadek Septiari (Universitas Pendidikan Ganesha, 2025)
Inclusive education in primary schools still faces challenges, particularly in school readiness to provide comprehensive inclusive services. The gap between policy and practice also limits optimal support for students with special needs.This study aims to critically analyze and evaluate the level of primary school readiness in implementing inclusive education based on established indicators. This research employed a quantitative approach with a descriptive evaluative design. The research subjects consisted of 1 principal and 6 teachers, while the instrument trial involved 10 respondents. Data were collected through observation, questionnaires, and documentation using structured observation sheets and survey instruments. Data analysis was conducted using quantitative descriptive statistics with percentage techniques. The findings indicate that the level of school readiness in implementing inclusive education is categorized as moderate, with 73.3% of the indicators fulfilled, while 26.7% remain unmet. These results suggest that although most components have been established, several critical aspects still require improvement, particularly in infrastructure provision, teacher competence, and institutional policy support. In conclusion, primary school readiness in implementing inclusive education has not yet reached an optimal level and requires strategic interventions to achieve ideal standards. The implications of this study highlight the urgency of strengthening policies, enhancing teacher competencies, and providing adequate facilities to support sustainable and high-quality inclusive education.